2008
DOI: 10.1152/ajpgi.00584.2007
|View full text |Cite
|
Sign up to set email alerts
|

Topological assessment of oatp1a1: a 12-transmembrane domain integral membrane protein with three N-linked carbohydrate chains

Abstract: Organic anion transport protein 1a1 (oatp1a1), a prototypical member of the oatp family of highly homologous transport proteins, is expressed on the basolateral (sinusoidal) surface of rat hepatocytes. The organization of oatp1a1 within the plasma membrane has not been well defined, and computer-based models have predicted possible 12- as well as 10-transmembrane domain structures. Which of oatp1a1's four potential N-linked glycosylation sites are actually glycosylated and their influence on transport function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 30 publications
4
41
1
Order By: Relevance
“…In 2008, the 12 TM domain structure of rOATP1A1 was confirmed using site-directed mutagenesis of putative N-glycosylation sites (P. Wang, Hata, Xiao, Murray, & Wolkoff, 2008). It was demonstrated that rOATP1A1 was N-glycosylated in the second and fifth extracellular loop, and that the unglycosylated protein was retained intracellularly and thus caused reduced transport function (P. Wang, et al, 2008). Similar results were recently published for hOATP1B1 (Yao et al, 2012).…”
Section: Structural Information On Oatps General Structuresupporting
confidence: 58%
See 1 more Smart Citation
“…In 2008, the 12 TM domain structure of rOATP1A1 was confirmed using site-directed mutagenesis of putative N-glycosylation sites (P. Wang, Hata, Xiao, Murray, & Wolkoff, 2008). It was demonstrated that rOATP1A1 was N-glycosylated in the second and fifth extracellular loop, and that the unglycosylated protein was retained intracellularly and thus caused reduced transport function (P. Wang, et al, 2008). Similar results were recently published for hOATP1B1 (Yao et al, 2012).…”
Section: Structural Information On Oatps General Structuresupporting
confidence: 58%
“…Immunostaining was only observed in detergent permeabilized cells (Abe et al, 2001), confirming a topology with both termini on the cytoplasmic side of the membrane. In 2008, the 12 TM domain structure of rOATP1A1 was confirmed using site-directed mutagenesis of putative N-glycosylation sites (P. Wang, Hata, Xiao, Murray, & Wolkoff, 2008). It was demonstrated that rOATP1A1 was N-glycosylated in the second and fifth extracellular loop, and that the unglycosylated protein was retained intracellularly and thus caused reduced transport function (P. Wang, et al, 2008).…”
Section: Structural Information On Oatps General Structurementioning
confidence: 96%
“…The superfamily is composed of six families based on 40% amino acid sequence identity divided into subfamilies that have 60% amino acid homology (Iusuf et al, 2012;Hagenbuch and Stieger, 2013). OATP family members are expressed in multiple organs, including the brain, heart, kidney, intestine, and liver, and they share structural similarities that include predicted 12 transmembrane domains (Wang et al, 2008;Hagenbuch and Stieger, 2013) and 3-4 N-linked glycosylation sites (Wang et al, 2008;Yao et al, 2012). Reduced transport activity of OATPs, accompanied by adverse drug reactions, have been described with Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoglycosylation of Oatp1a1, using the glycosylation inhibitor tunicamycin, causes intracellular retention and diminished transport of taurocholate in X. laevis oocytes . Both membrane targeting and functional activity of Oatp1a1 are regulated by the extent of N-glycosylation Wang et al, 2008c). Similar to the post-translational regulation of uptake transporters, apically expressed efflux transporters Mrp2 , BCRP (Mohrmann et al, 2005), Bsep (Mochizuki et al, 2007), and MDR1 are regulated by glycosylation and cellular trafficking.…”
Section: B Glycosylationmentioning
confidence: 93%